Effect of Wii Fit Exercise With Balance and Lower Limb Muscle Strength in Older Adults: A Meta-Analysis - Liu, Haoyan; Xing, Yu; Wu, Ying (Frontiers in Medicine, 2022)
Background Falls and fall-related injuries are not uncommon among older adults and may lead to serious health deterioration and decreased quality of life. Numerous types of physical activity have been proposed to improve balance and strength in older adults with varying degrees of success. Nintendo's Wii Fit video exergame uses body movement as a game controller and provides real-time feedback for games designed to enhance balance and muscle strength. However, whether Wii Fit exercise improves the balance and lower limb muscle strength of older adults remains uncertain. Objective To evaluate the current literature by using meta-analyses to assess whether Wii Fit exercise is associated with improved balance and lower limb muscle strength in older adults. Methods We searched PubMed, EMBASE, Web of Science, China National Knowledge Infrastructure, and Wanfang Data from inception to February 16, 2022, for relevant studies and conducted a manual search of the literature. Data extraction of the included studies were independently performed by two authors. The methodologic quality of each included study was assessed using the Physical Therapy Evidence Database (PEDro) scale. Meta-analyses were conducted using Review Manager 5.3. Results Of 991 articles initially identified, 10 articles (379 participants; aged ≥65 years, range 65–92 years; 188 participants in Wii Fit exercise groups, and 191 participants in control groups), including 8 randomized controlled trials, were assessed in this meta-analysis. The methodologic quality of the included studies evaluated with the PEDro average score was 6.4 and ranged from 5 to 8 points, indicating moderate quality. Compared with no exercise, Wii Fit exercise was associated with significant improved scores on the Berg Balance Scale, which evaluates functional balance (mean difference, 1.38; 95% CI, 0.61–2.16; I2 = 31%; P = 0.0005) and on the Timed Up and Go test, which evaluates static and dynamic balance (standardized mean difference, −0.51; 95% CI,−0.88 to −0.14; I2 = 52%; P = 0.007). However, for the three studies assessed, Wii Fit exercise did not significantly improve scores on the 30-s chair stand test, which evaluates the functional strength and endurance of the lower limb muscles (mean difference, 0.82; 95% CI, −0.14 to 1.77; z = 1.68; P = 0.09). Conclusions Our findings indicated that Wii Fit exercise is an effective approach to improve functional, static, and dynamic balance among older adults. Additional meta-analyzes with higher numbers of randomized controlled trials are suggested to confirm the benefits of Wii Fit exercise on balance in older adults, to establish whether functional strength and endurance of lower limb muscles are improved, and to explore the relationship between improved balance and fall prevention in this population.